Use of Participatory Forest Management as a Strategy for Sustainability of Kazimzumbwi and Pugu Forest Reserves, Tanzania - Mkhai, E M; Nawe, J; Manda, P A (University of Dar es Salaam Library Journal, 2017)
This study investigated the strategies for improving access to and use of information for forest management with particular reference to Kazimzumbwi and Pugu forest reserves in Coast Region located in the Pugu Hills area, about 20 km south-west of Dar es Salaam, in Tanzania. The review of literature and preliminary findings indicate that the majority of the people in developing countries, especially in rural areas depend on forests for multiple purposes such as construction materials, medicine, fodder, fuel wood, and domestic utensils. Moreover, the levels of forest degradation and deforestation are on the increase due to population pressure on forest resources, economic activities and climate change which are major challenges threatening forest resources. The findings also indicate that the Tanzania government recognises Participatory Forest Management (PFM) as a right strategy for effective forest management and sustainable forest use. Although PFM plays a central role in Tanzania ' s forest laws and policies, there is still a high rate of deforestation and forest degradation resulting in the reduction of forests to almost a half of the forests because of illegal activities. This could, to some extent, be attributed to rural communities ' inadequate access to and use of information for forest management. Since it is acknowledged that access to and use of information is critical in forest management it is recommended that the flow of information be closely monitored to minimise any obstructions. Secondly, the information communicated should be repackaged for ease of access and use by the majority of people, especially the targeted group in rural areas, who cannot understand scientific information. Thirdly, since general mass media, groups such as youth and women, awareness campaigns, and involvement in civil society activities are the real information transmission belts in communities, which bring immediate positive impacts, they should be effectively used by forest agencies.